Thermal control mechanism of ventilated–closed block layer composite embankment of expressway in warm permafrost regions - Yuan, Chang; Yu, Qi-hao; Li, Dong-wei; Chen, Xin; Qian, Jin; Wang, Zhenhua; Lai, Yuan-ming (Canadian Geotechnical Journal, 2023)
This study reveals the thermal control mechanism of a ventilated–closed block layer composite embankment structure by analyzing the heat transfer and temperature change based on the measured data of the high-grade highway experimental engineering in the Beiluhe area of the Qinghai–Tibet Plateau. During the cold season, natural convection occurred in the block layer when the upper boundary temperature was approximately 2 °C lower than that of the bottom boundary. In addition, heat from the foundation was transferred upwards through the block layer via heat convection. During the warm season, air inside the block layer was almost static, and external heat was transferred downwards through the block layer via heat conduction. The equivalent thermal conductivity of the block layer in the cold season was approximately 17.4 times that of the warm season, and heat release through the block layer was 9.65 times that of heat absorption, exhibiting a thermal semiconductor effect. The results show that the frozen soil foundation was in net exothermic state, the permafrost table continuously rose, and the mean annual soil temperature continuously decreased above 14 m depth. This research can contribute to thermal control technology development and construction scheme selection of expressway in permafrost regions.